Lesión del ligamento cruzado anterior: pautas diagnósticas. - Pachar Brito, Damián Vinicio (Machala: Universidad Técnica de Machala, 2023)
In the world of sports, football entails great physical demands and strict discipline, which is why it has an impact on an increase in injuries among athletes, one of which is the rupture of the Anterior Cruciate Ligament (ACL). This is the most feared fracture for footballers. “It is estimated that 200,000 ACL-related injuries occur annually in the United States, with approximately 95,000 ACL tears. Approximately 100,000 ACL reconstructions are performed each year. The incidence of anterior cruciate ligament injury is higher in people who participate in high-risk sports such as basketball, skiing, and soccer. When the frequency of participation is considered, a higher prevalence of injuries is observed in women than in men, at a rate between 2.4 and 9.7 times higher for women. (1) Its recovery takes a long time, in addition to the therapeutic processes that are carried out to be able to return to play with stability, however the possible consequences that said fracture can leave are uncertain, since recovery can occur with false positive in the athlete. Objective To determine the diagnostic guidelines in the injury of the Anterior Cruciate Ligament (ACL) of the knee. Methodology Descriptive study, evidenced in a systematic bibliographic review, where the analysis of scientific articles from various sources was carried out, such as medical journals, articles and websites with high scientific impression from the last 5 years.
En el mundo del deporte, el fútbol, conlleva una gran demanda del físico y una estricta disciplina, motivos por el cual repercute en un, aumento de las lesiones de los deportistas, una de ellas es la rotura del Ligamento Cruzado Anterior (LCA). esta es la fractura más temible por los futbolistas. “Se estima que anualmente se producen 200.000 lesiones relacionadas con el LCA en los Estados Unidos, con aproximadamente 95.000 roturas del LCA. Cada año se realizan aproximadamente 100.000 reconstrucciones del LCA. La incidencia de lesión del ligamento cruzado anterior es mayor en personas que participan en deportes de alto riesgo como baloncesto, esquí y fútbol. Cuando se considera la frecuencia de participación, se observa una mayor prevalencia de lesiones en las mujeres que en los hombres, a una tasa entre 2,4 y 9,7 veces mayor para las mujeres”. (1) Su recuperación conlleva de mucho tiempo, además de los procesos terapéuticos que se llevan a cabo para poder regresar a jugar con estabilidad, sin embargo las posibles secuelas que puede dejar dicha fractura son inciertas, ya que se puede dar una recuperación con falsos positivos en el deportista. Objetivo Determinar las pautas diagnosticas en la lesión del Ligamento Cruzado Anterior (LCA) de la rodilla. Metodología Estudio descriptivo, evidenciado en una revisión bibliográfica sistemática, donde se realizó el análisis de artículos científicos de diversas fuentes, como revistas médicas, artículos y sitios web de alta impresión científica de los últimos 5 años.
Keywords: RODILLA; TRAUMATISMO; LIGAMENTO CRUZADO ANTERIOR; ARTICULACION